2000
DOI: 10.1161/01.cir.102.17.2100
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Plasma C-Reactive Protein Are Associated With Decreased Graft Survival in Cardiac Transplant Recipients

Abstract: These findings suggest that elevated plasma levels of CRP are associated with subsequent allograft failure in cardiac transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 60 publications
(39 reference statements)
4
47
0
2
Order By: Relevance
“…The elevation of CRP levels is considered to be a strong predictor of development of CAV and its elevation is associated with subsequent allograft failure in cardiac transplant recipients [4,5]. Likewise, a higher BNP level in patients long after heart transplantation is associated with CAV and allograft dysfunction and represents an independent predictive risk of cardiovascular death [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevation of CRP levels is considered to be a strong predictor of development of CAV and its elevation is associated with subsequent allograft failure in cardiac transplant recipients [4,5]. Likewise, a higher BNP level in patients long after heart transplantation is associated with CAV and allograft dysfunction and represents an independent predictive risk of cardiovascular death [6].…”
Section: Discussionmentioning
confidence: 99%
“…Auflage, 190 S., 25 Abb., 5 Zusammenfassend bietet das vorliegende Buch einen sehr guten, umfassenden Überblick über die Tätigkeit als Honorararzt und ist jedem zu empfehlen, der sich mit dem Gedanken trägt, in dieser zunehmend attraktiven Beschäftigungs-form als Arzt tätig zu werden.…”
Section: Honorararzt -Flexibilität Und Freiberuflichkeitunclassified
“…35 Elevated levels of C-reactive protein, a sensitive marker of systemic inflammation, have been associated with the development of CAV 36 -38 and predict graft dysfunction. 37,39 Elevated plasma levels of BNP, which reflect wall stress and structural remodeling of the graft, have also been correlated with the development of CAV in the late post-HT phase. 40 The hypothesis of this study was that vWF, as a marker of endothelial dysfunction/activity, would be elevated in patients who develop the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of CRP to induce TF expression 10 may explain the recently reported association between elevated levels of CRP and decreased graft survival in cardiac transplantation patients. 6 The association between elevated TF expression and CAV could lead to several potential therapeutic strategies to either retard or prevent the progression of CAV. We have shown that TF activity is increased on the smooth muscle and endothelial cell surface in response to oxidant stress, such as that initiated by hydrogen peroxide and lipid hydroperoxides.…”
Section: Yen Et Al Tissue Factor and Cardiac Allograft Vasculopathymentioning
confidence: 99%
“…6,7 Our group and others have demonstrated in vascular cells that tissue factor (TF), a 47-kd cell membrane-bound glycoprotein that initiates the extrinsic coagulation cascade leading to thrombin formation by binding factor VII, is upregulated in response to oxLDL. 8,9 CRP has also been shown to induce TF expression in monocytes.…”
mentioning
confidence: 99%